2019
DOI: 10.1213/ane.0000000000003921
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Respiratory or Vasopressor Support and/or Death as a Proposed Composite Outcome Measure for Perioperative Care Research

Abstract: Authors' Contributions Toshiyuki Mizota: This author conceptualized and designed the study, collected and analyzed the dataset, and drafted the manuscript. Li Dong: This author helped design the study, analyzed and interpreted data, and critically revised and approved the manuscript. Chikashi Takeda: This author helped design the study, analyzed and interpreted data, and critically revised and approved the manuscript. Atsuko Shiraki: This author analyzed and interpreted data and critically revised and approved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 34 publications
(44 reference statements)
0
8
0
Order By: Relevance
“…Vasoactive agents are widely used in the perioperative period and are administered according to blood pressure and other hemodynamic goals 33,34 . Mizota et al reported that in a retrospective cohort study of 2776 patients who underwent major abdominal surgery, postoperative invasive respiratory or vasopressor support was associated with higher hospital mortality and lower long-term survival when limiting their analysis to 30-day survivors 35 . In our study, a 30-day mortality rate was also found to be significantly higher in patients who received inotrope/vasoconstrictor drug support due to hemodynamic instability in the first 24 postoperative hours.…”
Section: Discussionmentioning
confidence: 99%
“…Vasoactive agents are widely used in the perioperative period and are administered according to blood pressure and other hemodynamic goals 33,34 . Mizota et al reported that in a retrospective cohort study of 2776 patients who underwent major abdominal surgery, postoperative invasive respiratory or vasopressor support was associated with higher hospital mortality and lower long-term survival when limiting their analysis to 30-day survivors 35 . In our study, a 30-day mortality rate was also found to be significantly higher in patients who received inotrope/vasoconstrictor drug support due to hemodynamic instability in the first 24 postoperative hours.…”
Section: Discussionmentioning
confidence: 99%
“…We consecutively selected patients who underwent surgery under the care of anesthesiologists at Kyoto University Hospital (1121 beds). We have published several studies using the Kyoto-IMPACT database 20 , 21 . We included adult female patients aged 18 years or older who underwent gynecologic laparoscopic surgery (i.e., adnexal surgery and/or hysterectomy) at Kyoto University Hospital between January 2012 and December 2017.…”
Section: Methodsmentioning
confidence: 99%
“…We identified eligible patients using the Kyoto University Hospital IMProve Anesthesia Care and ouTcomes (Kyoto-IMPACT) database, which is designed to identify the relationship between intraoperative respiratory and circulatory parameters and postoperative outcomes. We have previously published several papers using this database [ 10 , 11 , 12 ]. We excluded patients younger than 18 years, patients admitted to the intensive care unit postoperatively, and patients undergoing epidural anesthesia.…”
Section: Methodsmentioning
confidence: 99%